1995
DOI: 10.1042/bj3060241
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-inactivation analysis of the Na+/bile acid co-transport system from rabbit ileum

Abstract: The functional-unit molecular size of the Na+/bile acid cotransport system and the apparent target size of the bile-acid-binding proteins in brush-border membrane vesicles from rabbit ileum were determined by radiation inactivation with high-energy electrons. The size of the functional transporting unit for Na(+)-dependent taurocholate uptake was determined to 451 +/- 35 kDa, whereas an apparent molecular mass of 434 +/- 39 kDa was measured for the Na(+)-dependent D-glucose transport system. Proteins of 93 kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The Na-dependent uptake involves the ileal apical bile acid transporter ASBT, the most important transporter in humans and mice (26,27). This transporter has different affinities to different bile acid species and operates as a homotetramer that interacts with bile acid transport protein (28). The Na-independent uptake involves the Oatp3 transporter, also with different affinities to different bile acid species, which localizes to the apical membrane of jejunal enterocytes (29).…”
Section: Discussionmentioning
confidence: 99%
“…The Na-dependent uptake involves the ileal apical bile acid transporter ASBT, the most important transporter in humans and mice (26,27). This transporter has different affinities to different bile acid species and operates as a homotetramer that interacts with bile acid transport protein (28). The Na-independent uptake involves the Oatp3 transporter, also with different affinities to different bile acid species, which localizes to the apical membrane of jejunal enterocytes (29).…”
Section: Discussionmentioning
confidence: 99%
“…For an unequivocal localization of the ligand binding a covalent cross-linking of the ligand to the peptide backbone and subsequent determination of the cross-linking position is necessary. The ileal Na ϩ /bile acid cotransport system in intact ileal tissue is a heteromeric protein complex of 451 kDa composed of several transporter units and associated ileal lipidbinding proteins (3,6). Because the structure and composition of the ileal Na ϩ /bile acid cotransport system in recombinant cell lines is not known and because functional differences of transporters found in intact tissues and recombinant cell lines were reported (22), we decided to photolabel the ileal Na ϩ /bile acid cotransporter in situ using freshly isolated rabbit ileal brush border membrane vesicles with subsequent determination of the attachment site.…”
Section: Discussionmentioning
confidence: 99%
“…Materials-Photoaffinity labeling was carried out with the photoreactive bile acid analogue 2-(7,7-azo-3␣,12␣-dihydroxy-5␤-[3␤- 3 H]cholan-24-oylamino)-ethane-sulfonic acid (specific radioactivity, 20.25 Ci/mmol) synthesized as described elsewhere (16,17). Acrylamide, N,NЈ-methylene bisacrylamide and Serva Blue R-250 were from Serva (Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis of the Na ϩ /bile acid cotransport systems in ileocytes and hepatocytes by target size analysis revealed that these transport systems are in their functional states protein complexes composed of several subunits (29 -31). The rabbit ileal Na ϩ /bile acid cotransport system revealed a functional molecular mass of 451 Ϯ 35 kDa (31) being probably composed of four integral membrane proteins of 93 kDa (identified as dimers of the Na ϩ /bile acid cotransporting protein (19)) and four cytoplasmically attached 14-kDa peripheral membrane proteins (19,22,31). The 14-kDa protein, the ileal lipid-binding protein (ILBP), 1 has originally been identified as a predominant bile acid binder in the cytosol of ileocytes (21,(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%